2020
DOI: 10.1098/rsos.191722
|View full text |Cite
|
Sign up to set email alerts
|

Forest habitat parameters influence abundance and diversity of cadaver-visiting dung beetles in Central Europe

Abstract: Dung beetles provide crucial ecosystem services and serve as model organisms for various behavioural, ecological and evolutionary studies. However, dung beetles have received little attention as consumers of large cadavers. In this study, we trapped copronecrophagous dung beetles on above-ground exposed piglet cadavers in 61 forest plots distributed over three geographically distinct regions in Germany, Central Europe. We examined the effects of land use intensity, forest stand, soil characteristics, vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 71 publications
5
31
0
Order By: Relevance
“…The habitat effect and lack of locality effect on dung beetle assemblages are probably linked to vegetation characteristics. Several studies showed that vegetation structure (e.g., plant diversity [62]), fine-scale heterogeneity in grazing intensity [63], or vegetation cover [64] highly influenced dung beetle assemblages. Our results on habitat and locality can be explained on the assumption that differences between forests or pastures or wood pastures are smaller across locations than among the three habitat types within a given location.…”
Section: Discussionmentioning
confidence: 99%
“…The habitat effect and lack of locality effect on dung beetle assemblages are probably linked to vegetation characteristics. Several studies showed that vegetation structure (e.g., plant diversity [62]), fine-scale heterogeneity in grazing intensity [63], or vegetation cover [64] highly influenced dung beetle assemblages. Our results on habitat and locality can be explained on the assumption that differences between forests or pastures or wood pastures are smaller across locations than among the three habitat types within a given location.…”
Section: Discussionmentioning
confidence: 99%
“…Our former study showed that A. stercorosus is mainly attracted to the progressed (post-bloating and advanced decay) stages of decomposing vertebrate cadavers [ 34 ]. Therefore, we aimed to attract A. stercorosus in field assays with a synthetic cadaver bouquet from a post-bloating decomposition stage.…”
Section: Methodsmentioning
confidence: 99%
“…This black beetle with its metallic blue coloration is relatively large (12–19 mm) and is active between June and September as a super-dominant species in thicket and in pole timber and mature stands [ 29 , 30 , 31 , 32 ]. Anoplotrupes stercorosus , described as a copronecrophagous species, mainly feeds on the fluid parts of animal excrement or carrion [ 33 , 34 ]. Several studies have shown the feeding preferences of A. stercorosus linked to herbivore dung.…”
Section: Introductionmentioning
confidence: 99%
“…Land-use intensity and the consequential environmental changes of a given habitat may influence beetle communities directly by reducing their population size or indirectly by affecting habitat heterogeneity, habitat availability, or prey (and consequently carcass) availability ( Lange et al 2014 ). Indeed, carabid, staphylinid, and dung beetle communities have all been documented to be affected by human management activities, although both negative and positive effects have been reported ( du Bus de Warnaffe and Lebrun 2004 , Vanbergen et al 2005 , Niemelä et al 2007 , Fuller et al 2008 , da Silva et al 2008 , Barragán et al 2011 , Lange et al 2014 , Frank et al 2017 , von Hoermann et al 2020 ). In our current study, we did not reveal any negative effects of forest management activities on the amount of attracted beetles, which means that neither the emission nor the transmission of the sex pheromone is considerably impaired, nor is there an influence on the prevailing abundance of beetles.…”
Section: Discussionmentioning
confidence: 99%